Implementation of Sibghah Al-Washliyah Values in Islamic Religious Education Learning - Haidir Haidir; Muhammad Hizbullah; Azrai Harahap; Ardat Ardat; Nur Jannah (Hikmah, 2025)
This study is motivated by the importance of strengthening students’ Islamic identity and character through the internalization of Al-Washliyah’s distinctive values in Islamic Religious Education learning. Sibghah Al-Washliyah, which encompasses the values of tawhid, scholarship, morality, religious moderation, and the spirit of da‘wah, is viewed as a strategic foundation for shaping student character at Universitas Muslim Nusantara Al-Washliyah. This study aims to analyze the implementation of Sibghah Al-Washliyah values in the learning process of Islamic Religious Education. The research employs a qualitative approach with a descriptive study design. Data were collected through in-depth interviews with lecturers and students, observation of the learning process, and documentation of institutional policies, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that lecturers have a relatively good understanding of Sibghah Al-Washliyah values, although their implementation varies. Values such as istiqamah, akhlakul karimah, mujahadah, and religious moderation are integrated into learning materials and instructional methods. The implications of this study emphasize the need to continuously strengthen the implementation of Sibghah Al-Washliyah values through institutional policies and more systematic learning development.